Thebes at the time of the Catalans a deposit between the Ismenion Hill and the Elektra Gate - Kondyli, F; Larson, S; Baker, J; Liard, F; Daly, K; Charami, A; Aravantinos, V (American School of Classical Studies at Athens, 2020)
A bothros excavated in 2011 in the Thebes parking area revealed large quantities of late-13th- to mid-14th-century a.d. domestic waste, including glazed table wares, coarse wares, a small coin hoard, and other everyday objects, highlighting aspects of economic activities, domestic life, and waste management in Thebes at this time. The assemblage also offers a rare glimpse of Thebes amid significant political change: the Catalan takeover of the city and the wider area of central Greece in a.d. 1311. Both the richness of the bothros's material and its location outside the city walls argue against canonical notions of the abandonment of Thebes and economic stagnation caused by the Catalan occupation.